Al-Qur’an: Memerangi Illiteracy, Mencipta Peradaban Ilmu Pengetahuan - Ali Romdhoni (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
This article would like to show that the Qur’an has influenced the development of Islamic civilization and sciences. In order to prove that, this article will tackle two questions, firstly when did the Arabic literacy tradition develop in Arab community, and secondly, which factors did influence the development of Islamic civilization. This article argues against Ibn Khaldun (d. 808 H), who claims that literacy depends on the economic development. According to the author of this article, this condition is not relevant with the Arab community, since the economi condition of the Arabs at the time was not prosperous. This article argues that piety, religiousity, and Muslim dedication to learn from the Qur’an which influence the development of Islamic civilization.